Kinetics of nitric oxide adsorption on Pd(111) surfaces through molecular beam experiments: a quantitative study - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S.; Prasad, Sudarsan D. (Journal of Physical Chemistry C, 2011)
A detailed kinetic picture derived by molecular beam studies of the adsorption-desorption of the NO/Pd(111) system is presented. Numerical simulations and detailed kinetic analysis show that the precursor state model of adsorption provides a valid picture of the sticking coefficient variation with surface coverage, especially at low temperatures. At higher temperatures, the precursor model gives way to the Langmuir molecular model of adsorption. All the parameters of the precursor state model have been quantified. Temperature programmed desorption (TPD) studies further show that there is a slight repulsive interaction between adsorbed NO molecules and there is only a negligible fraction of dissociated molecules on the surface for temperatures less than 500 K, as the Pd(111) surface is defect free. A Bragg-Williams (BW) lattice gas model with repulsive interactions, within the framework of mean field approach (MFA), is shown to describe the TPD spectra reasonably well.